Synthesis and Applications of Polymeric Reagent p-Substituted Triphenylamine - Abu-Abdoun, Ideisan I. (Journal of Research Updates in Polymer Science, 2021)
Chemical modification of chloromethylstyrene - styrene copolymer throughout reaction of p-substituted carboxylic acid group of bis-(4,4`-dibromo)-4``-triphenylamine carboxylic acid with the chloromethyl group attached to a phenyl group was carried out on soluble copolymer and polymeric cross-linked copolymer. Chemical oxidation of the neutral p-substituted triphenylamine with antimony pentachloride in dichloromethane solvent gives the corresponding cation - radical salt with the counter ion antimony hexachloride (SbCl6-). The isolated deep blue color cation radical salt is soluble or in insoluble (resin) form in the copolymer was used as a thermal cationic initiator for the polymerization of epoxy and vinyl monomers at room temperature. The cation radical resin showed good activity and stability compared to the soluble polymeric cation radical, both can initiate the cationic polymerization of cyclohexene oxide and N-vinylcarbazole in dichloromethane at room temperature.